Strategic reforms for agricultural growth in Pakistan - Faruqee, Rashid (Ed.); World Bank (Washington) (Washington World Bank, 1991)
The book contains the past performance of Pakistan's agriculture facing the sector in recent years.Agriculture also affects economic growth structural adjustment,interanl and external balances,poverty reduction and natural resources management significant
Keywords: Agriculture-Pakistan; Agricultural development projects; Agriculture and state-Pakistan; Agriculture-Economic aspects-Pakistan